New lymph node staging for rectal neuroendocrine tumors. Issue 1 (27th November 2018) - Fields, Adam C.; McCarty, Justin C.; Ma‐Pak, Linda; Lu, Pamela; Irani, Jennifer; Goldberg, Joel E.; Bleday, Ronald; Chan, Jennifer; Melnitchouk, Nelya
Abstract : Background and Objectives: Current guidelines of the American Joint Commission on Cancer (AJCC) for rectal neuroendocrine tumors (NETs) classify tumor nodal status as N0/N1. This staging does not take into consideration the number of positive lymph nodes. The goal of this study is to determine how the number of positive lymph nodes affects the prognosis for patients with rectal NETs. Methods: The National Cancer Database was used to identify patients with rectal NETs who underwent rectal resection. Nearest‐neighborhood grouping was used to classify patients by survival to create a new nodal staging system. Results: There were 687 patients with rectal NETs. There were distinct 5‐year survival estimates for patients with N0 [81.8% (95%CI:77.1%‐85.6%)], N1 (1‐4 positive lymph nodes) [57.8% (95% confidence interval (CI: 51.2%‐63.9%)] and N2 (≥5 positive lymph nodes) [32.6% (95%CI:25.1%‐40.3%)] patients, P  < 0.0001. Distinct 5‐year survival estimates using the new nodal staging system was apparent for patients in the external validation set. After adjusting for predictors of survival in multivariable analysis, the new nodal stage remained an independent predictor of overall survival. Conclusions: The number of positive locoregional lymph nodes is an independent prognostic factor in rectal NETs. The next AJCC edition should consider classifying patients with rectal NETs as N0, N1, and N2 to provide better estimates of survival for patients.